2015
DOI: 10.1007/s10461-015-1003-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV Housing Services on Engagement in Care and Treatment, New York City, 2011

Abstract: The federal Housing Opportunities for Persons with AIDS (HOPWA) program addresses housing needs of low-income persons living with HIV/AIDS (PLWHA). The New York City (NYC) Department of Health and Mental Hygiene oversees 22 HOPWA contracts for over 2,400 clients, and manages the NYC HIV Registry. HOPWA clients (N = 1,357) were matched to a random 20 % sample of other PLWHA (N = 13,489). Groups were compared on HIV care retention, viral suppression, and rebound. HOPWA clients were, on average, 3 years younger a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
2
9
2
Order By: Relevance
“…A recent study tracked treatment outcomes for PLWH who received housing supports via the federal Housing Opportunities for People with AIDS (HOPWA) program, comparing participants to a random sample of PLWH who were not HOPWA recipients. While this study found significant increases in retention in care for the intervention group, no differences were found in rates of viral suppression (26). Nonetheless, a systematic review of 152 studies that examined associations between housing and clinical outcomes (including treatment adherence and viral suppression) found an independent effect of housing on HIV health outcomes for homeless or formerly homeless PLWH (29).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…A recent study tracked treatment outcomes for PLWH who received housing supports via the federal Housing Opportunities for People with AIDS (HOPWA) program, comparing participants to a random sample of PLWH who were not HOPWA recipients. While this study found significant increases in retention in care for the intervention group, no differences were found in rates of viral suppression (26). Nonetheless, a systematic review of 152 studies that examined associations between housing and clinical outcomes (including treatment adherence and viral suppression) found an independent effect of housing on HIV health outcomes for homeless or formerly homeless PLWH (29).…”
Section: Discussioncontrasting
confidence: 69%
“…A study recently examined treatment outcomes for PLWH who received housing supports via the federal Housing Opportunities for People with AIDS (HOPWA) program, comparing participants to a random sample of PLWH who were not HOPWA recipients. This study found significant increases in retention in care for the intervention group, however, no differences in rates of viral suppression were noted (26). In addition, the study was limited to a specific subset of PLWH, namely, those receiving HOPWA support.…”
Section: Introductionmentioning
confidence: 72%
“…A strength of this analysis is that we used a novel strategy of combining HCV programme and surveillance data for evaluation purposes. Similar analyses have been conducted using HIV surveillance data to evaluate HIV programmes, 39…”
Section: Discussionmentioning
confidence: 94%
“…A strength of this analysis is that we used a novel strategy of combining HCV programme and surveillance data for evaluation purposes. Similar analyses have been conducted using HIV surveillance data to evaluate HIV programmes, but to our knowledge, this is the first evaluation to examine the impact of HCV care coordination using a demographically similar comparison group reported to a city‐wide surveillance registry. This novel method offers a relatively inexpensive approach for local health departments to support HCV programme evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…These trends may be reflective of other individual-level factors such as homelessness, substance abuse, and more fragmented care in general, among patients with multiple comorbid conditions. Furthermore, this more vulnerable group may have had seemingly higher retention in care as they may have returned to care more often for follow-up visits based on provider concerns about client health, fear of losing contact with the most transient clients, or based on receipt of more referrals to other clinics or specialists for their comorbid conditions [ 35 , 36 ]. However, while a higher proportion of these participants may have met the retention in care definition, their care patterns appear to reflect more disparate care, as meeting the definition did not translate into higher viral suppression.…”
Section: Discussionmentioning
confidence: 99%